Eksistensi Pencak Silat dalam Penciptaan Tari Tradisi Gaya Surakarta - Maryono Maryono (Institut Seni Indonesia Surakarta, 2010)
The wide range of pencak silat movements used in traditional Surakarta style dance represents their importance in the formation and enrichment of the variety of dance movements in this dance style, especially in the Keprajuritan or Military dance genre. The basic pencak silat movements used for defence, dodging, and stabbing, as well as patterns of combat, have been absorbed and developed in the field of traditional dance to become movements with an expressive quality.Keywords:Â Pencak silat, basic, enrichment, traditional dance, and military dance.